Case Report: The Use of Rituximab in Antibody-Negative Autoimmune Encephalitis - Park, Soo-Hyun; Kim, Yong-Chan (Frontiers in Neurology, 2021)
Antibody-negative autoimmune encephalitis (AE) is challenging to diagnose because clinically suspected antibody-negative AE cases are difficult to confirm. If not treated properly, like antibody-positive AE, antibody-negative AE can cause irreparable damage to patients. Previously, immunotherapy was effective in treating patients with antibody-negative AE. We present the case of a 63-year-old man who was admitted to our hospital with altered cognition. He was diagnosed with antibody-negative AE based on CSF, brain MRI, and B-cell counts; autoimmune diseases with similar clinical symptoms were ruled out. He was treated with immunotherapy, especially rituximab, for antibody-negative AE. After 3 weeks of treatment, his mental state and brain MRI results, concomitant with a decrease in CD19+/CD20+ B-cell counts. This case report shows that patients with antibody-negative AE may respond to rituximab, similar to those with antibody-positive AE. Thus, potentially undetected antibodies could be responsible for the treatment outcome.